2020
DOI: 10.3390/foods9111674
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Consecutive Process of Pulsed Electric Field, Sous-Vide Cooking, and Reheating on the Properties of Beef Semitendinosus Muscle

Abstract: The effects of a consecutive process of pulsed electric field (PEF) treatment, sous-vide cooking, and reheating on the properties of beef semitendinosus muscle were investigated. Fresh meats were PEF-treated with different electric field strengths of 1.0, 1.5, and 2.0 kV/cm, and then the control and PEF-pretreated beef samples were sous-vide cooked at 60 °C for up to 24 h. The PEF pretreatment resulted in tenderization of the fresh meat proportional to the increase in the electric field strength. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The results showed that, at 3.50 kV/cm, the hardness, cohesiveness, chewiness, and elasticity of beef were significantly reduced compared to the control group. This is similar to the results of Jeong et al [87], which suggested that the shear force, chewiness, and hardness of beef decreased as the electric field intensity increased. Such a phenomenon may rely on the fact that PEF treatment could increase the degradation of troponin and pro-myosin in beef, resulting in improved tenderness.…”
Section: Pulsed Electric Fieldsupporting
confidence: 91%
“…The results showed that, at 3.50 kV/cm, the hardness, cohesiveness, chewiness, and elasticity of beef were significantly reduced compared to the control group. This is similar to the results of Jeong et al [87], which suggested that the shear force, chewiness, and hardness of beef decreased as the electric field intensity increased. Such a phenomenon may rely on the fact that PEF treatment could increase the degradation of troponin and pro-myosin in beef, resulting in improved tenderness.…”
Section: Pulsed Electric Fieldsupporting
confidence: 91%
“…[14]. The term "sous vide" is a French word that refers to the uniform cooking of food inside the food grade and heat-stable vacuumed pouches incubated in a circulating water bath with monitored conditions of temperature and time followed by chilled storage [15,16]. Sous vide cooking has been reported to enhance the quality attributes, inhibiting off-flavors from lipid oxidation, reducing aerobic bacteria and the risk of post-cooking contamination during storage [9,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can be confirmed by comparing the studies listed in Tables 1 and 2 , as they provide evidence of this effect. Furthermore, studies that have explored the combination of PEF and sous-vide cooking have observed a tenderization effect ( Jeong et al, 2020 ; Karki et al, 2023 ). According to Jeong et al (2020) , the PEF effect observed in raw beef Semitendinosus muscle was maintained even after sous-vide cooking (60°C, 1 h to 24 h).…”
Section: Tenderization Effects Of Pulsed Electric Field Treatmentmentioning
confidence: 99%
“…Furthermore, studies that have explored the combination of PEF and sous-vide cooking have observed a tenderization effect ( Jeong et al, 2020 ; Karki et al, 2023 ). According to Jeong et al (2020) , the PEF effect observed in raw beef Semitendinosus muscle was maintained even after sous-vide cooking (60°C, 1 h to 24 h). Karki et al (2023) conducted the PEF treatment and sous-vide cooking (60°C, 24 h and 36 h) on short ribs.…”
Section: Tenderization Effects Of Pulsed Electric Field Treatmentmentioning
confidence: 99%